Fabrikasi Kuku Bucket Ekskavator Baja Cor Ukuran 300×90×105 mm Lubang 30 mm, Kapasitas 0,25 Biji/Jam - Agung Cahyadi; Syamsul Hadi; Achmad Syarifudin Annawa; Ardita Firmansyah; Hadziq Fikri; Ihza Narayana Rosyadi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The problem faced lies in the excavator bucket nails that do not have standardized manufacturing procedures in the local casting industry, resulting in inconsistent product quality and high dependence on imported components. The purpose of fabrication is to obtain excavator bucket nails made of high Manganese cast steel (hadfield steel) measuring 300×90×105 mm with a hole diameter of 30 mm. The fabrication method includes: purchasing a 300×90×105 mm excavator bucket nail mold using one-piece casting method, preparing ASTM A128 Grade B-2 high Manganese steel, melting the steel with an induction furnace at a pouring temperature of 1480-1510°C, pouring the molten steel into a sand mold, dismantling and cutting the casting bowl and riser, drilling the dowel holes in stages up to a diameter of 30 mm, machining, finishing, solution annealing heat treatment at a temperature of 1080°C for 60 minutes, quenching in water, preparing and testing Charpy specimens, and inspecting the quality and dimensions of the product. The fabrication results are in the form of high manganese cast steel excavator bucket nails (hadfield steel) measuring 300×90×105 mm with a hole diameter of 30 mm, the total production cost is IDR 315,000/unit, the production process duration is 240 minutes/unit which implies that the excavator bucket nails can be used according to standards.